Cardio-diabetic protective effect of Telmisartan - Nandi, Shiladitya; Nag, Sourav; Ash, Trinanjan; V Chandra Shekhar (Medico Research Chronicles, 2021)
The antihypertensive drugs that are being used currently were primarily designed and developed to affect cellular and biochemical mechanisms that lead to increased blood pressure and do not address the underlying contributory factors like, disordered carbohydrate and lipid metabolism that often accompanies hypertension as part of the metabolic syndrome. The metabolic syndrome eventually leads to co-morbid conditions i.e., hypertension and type 2 diabetes mellitus. Both these conditions mechanistically share the common pathophysiological pathways in people who suffer from metabolic syndrome. PPAR-γ plays an important role in regulating carbohydrate and lipid metabolism and ligands for PPAR γ can improve insulin sensitivity, reduce triglyceride levels, and decrease the risk for atherosclerosis. Telmisartan is a well-established angiotensin II type 1 receptor (AT1) blocker along with an activator of the PPARγ receptor. Telmisartan has several pharmacological properties that distinguish it from other ARBs, like, the structural resemblance with pioglitazone which is a PPARγ ligand that is approved for the treatment of type 2 diabetes. Thus, telmisartan seems to be a suitable candidate for the management of CV risk reduction in patients with atherothrombotic disease or diabetes mellitus with end-organ damage. This article will discuss the mechanistic aspect of telmisartan that supports its utility in cardiac protection along with the outcome of different clinical trials.